(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
This article explores the development of a methodology aimed at enhancing the social competence of students through the use of ethnopedagogical models. Social competence, which encompasses students’ ability to communicate, collaborate, and engage in a diverse society, is increasingly important in modern education. The ethnopedagogical approach, rooted in cultural traditions and values, offers a unique framework for fostering these skills. The article examines existing literature on ethnopedagogy and social competence, details the proposed methodology, and discusses its potential applications in the educational process.